Development of an Electronic Database for Acute Pain Service Outcomes - Brandy L Love; Louise A Jensen; Donald Schopflocher; Ban CH Tsui (Pain Research and Management)
From mitigating complications during hospital stay to reducing the incidence of chronic pain, improving pain management positively impacts short- and long-term outcomes of treatment. Quality assurance has become the focus of many health care programs in an effort to confront the challenges presented by pain and its management. The analysis of treatment strategies and patient responses form the basis of a reflective, evidence-based practice, which can raise awareness of about the importance of adequate pain management. The capabilities of an electronic database can be exploited to organize large amounts of data, which can then be used to characterize symptoms and analyze treatment responses. However, the types of data to collect, the burden of data collection on workers, and costs must be considered before implementing an electronic database for research and/or everyday practice. This study tested the relevance and usability of an electronic database in an acute pain service by assessing several variables important to database development and evaluation.